Magnetic Resonance Imaging (MRI) Neurobiological Correlates of Cognitive Performance: Intracortical Myelin and Cortical Thickness - Elkhayat, Mazen (My University, 2025)
The cortex is a major focus of many studies into the relationship between brain structure and cognitive function due its involvement in higher-order processes. Many such studies have employed aggregate structural measures such as cortical thickness, with fewer studies focusing on the microstructure of the cortex. A relevant compositional feature of the cortex in this context is intracortical myelin (ICM), which facilitates communication between cortical regions. Although there is theoretical and indirect evidence to support a positive association between ICM and cognitive performance, this relationship has not been studied extensively in humans outside of the involvement of a few regions in select tasks. We aimed to characterize the relationship between cognitive performance and each of ICM and cortical thickness in the same sample, to evaluate whether ICM is related to performance on a variety of tasks commonly used in the context of cognitive assessment and to provide a more comprehensive understanding of cortical architecture in the emerging to middle adulthood age range. Using the longitudinal relaxation rate (R1) as a surrogate measure of ICM, magnetic resonance imaging (MRI) and neuropsychological data were collected from 78 healthy individuals, aged 16-43 years. Correlations between performance on each neuropsychological test and each of R1 and cortical thickness across 360 regions-of-interest (ROIs) were computed and mapped onto the cortical surface. While correlations varied across ROIs and tests, we found positive correlations between cognitive performance and R1 across a variety of ROIs and tasks, whereas there were more negative correlations between cognitive performance and cortical thickness on average. These results provide empirical support for the notion that ICM may help support cognitive function across various domains, and further our current understanding of cortical morphology in the age window between development and older age.